Impact of donor-acceptor morphology on the charge carrier generation in organic photovoltaic devices - Inche Ibrahim, Mohd Lukman (IOP Publishing, 2018)
We investigate the impact of donor-acceptor morphology on the generation of charge carriers in organic photovoltaic cells and photodiodes based on a recently proposed model. It is found that for devices with typical values of permittivity and actual charge carrier mobilities, the donor-acceptor morphology plays an important role in the charge carrier generation, practically at all operating electric fields. Higher permittivity and actual mobilities increase the charge carrier generation, and also decrease the effect of donor-acceptor morphology on the charge carrier generation. Although the donor-acceptor morphology is important for charge carrier generation in general, but having permittivity and/or actual mobilities that are significantly higher than the typical values are more desirable in order to maximize the charge carrier generation.